A mixed methods analysis of the impact of a positive psychology-based college readiness course on first-year college students in Vietnam - Phan, Khuc, author; Jennings, Louise, advisor; Gloeckner, Gene, advisor; Aragón, Antonette, committee member; Williams, Elizabeth, committee member (Colorado State University. Libraries, 2025)
This multiple-article dissertation presents a mixed-method study investigating the impact of a positive psychology-based College Readiness course on academic success among first-year college students in Vietnam. The course was developed in response to low retention rates and challenges faced by Vietnamese college students, aiming to reinforce factors associated with academic success, including psychological well-being, self-efficacy, and skills for effective learning. This study examined the effectiveness of this course in enhancing these outcomes. Through a systematic review of 32 ProQuest-indexed studies, Article One identified five key factors associated with college students' academic success: motivation and engagement, personality traits, self-efficacy, psychological well-being, and skills for effective learning. The review also examined the effectiveness of first-year support courses in addressing these factors. The findings of this chapter guided the development of the College Readiness course. Article Two presented a validation study for the PERMA-Profiler questionnaire, one of the instruments used to examine the effectiveness of the College Readiness course to ensure its appropriateness for assessing the psychological well-being of college students in Vietnam. Articles Three and Four reported on a convergent mixed methods study with a quasi-experimental approach, investigating the impact of the College Readiness course on Vietnamese college students' psychological well-being, self-efficacy, and self-confidence in key skills for learning. The study included 58 participants, with 36 in the experimental group and 22 in the control group. Quantitative data were collected using self-reported measures at three time points, while qualitative data were gathered through open-ended survey items and focus group interviews. The findings demonstrated that the course had a positive impact on self-efficacy and overall psychological well-being, with effects sustained six weeks post-completion. Additionally, most individual factors related to psychological well-being and self-confidence in learning skills showed significant improvements that persisted through the six-week follow-up. The qualitative data provided richer insights into the specific areas of impact and influential course elements. Article Five examined the relationships between the experimental students' IELTS scores at admission and these academic success factors prior to the College Readiness course, immediately after, and six weeks after the course ended. Collectively, these five articles contributed to the understanding of how a positive psychology-based College Readiness course can benefit Vietnamese college students by enhancing factors associated with their academic success. The results provide practical implications that can inform the design of first-year support programs, helping educators make well-informed decisions regarding the integration of positive psychology strategies to enhance students' academic success and support their transition to college in both the Vietnamese context and globally.
Keywords: college readiness; psychological well-being; self-efficacy; key learning skills; academic success; self-confidence